Pedagogical Implications of Integrating Indigenous Games for Development of Foundational Numeracy Skills - Bamara, Atul; Bamara, Poonam (THE PRIMARY TEACHER, 2025)
Numeracy is essential for navigating daily tasks, such as managing finances, interpreting data, making decisions based on numerical information and understanding mathematical concepts in various fields. Developing strong numeracy skills is crucial for success in education, career and everyday life. In India, there are various initiatives and missions aimed at improving foundational numeracy skills among children. Such games often incorporate elements of numeracy in various ways. Such games play an important role in preserving cultural identity, transmitting cultural knowledge, promoting social cohesion and fostering a sense of belonging within indigenous communities. They also offer valuable opportunities for learning, skill development and intergenerational exchange. As such, indigenous games hold significance not only as forms of entertainment but also as integral components of indigenous cultural heritage and identity. These games, deeply rooted in cultural traditions, offer valuable opportunities for developing numeracy skills among participants. This paper highlights the integration of indigenous games, while inculcating numeracy skills among foundational level learners